Health care professionals' knowledge and attitudes toward telemedicine - Bashir, Muhammad Salman; Lalithabai, Diana Selvamony; AlOtaiby, Shahad; Abu-Shaheen, Amani (Frontiers in Public Health, 2023)
Abstract Background: Telemedicine, the use of advanced communication technologies in health care systems, represents a step forward in the healthcare industry. For a successful implementation of such technologies, health care professionals need to have an adequate knowledge and a positive attitude towards telemedicine enforcement. The present study aims to examine the knowledge and attitude of health care professionals in King Fahad Medical City, Saudi Arabia, towards telemedicine. Methods This is a cross-sectional study conducted at a multicultural tertiary hospital, King Fahad Medical City, Saudi Arabia, between June 2019 and February 2020. During this period, 370 healthcare professionals, including doctors, nurses, and other allied healthcare professionals participated. Data was collected through a structured self-administered questionnaire. Results: Data analysis revealed that the majority of the participating health care professionals, that is 237 (63.7%) participants, had poor knowledge of telemedicine. Around 41 (11%) participants had good understanding, and 94 participants (25.3%) had excellent knowledge of the telemedicine technology. The participants’ overall attitude towards telemedicine reflected a high attitude score with a mean of 3.26. The overall mean attitude scores were significantly different (P < 0.001) among the other professions, where physicians, allied health care professionals, and nurses scored 3.69, 3.31, and 3.07 respectively. The coefficient of determination (R2) was used to explain the variation in the attitude towards telemedicine and found that education (12.4%) and nationality (4.7%) had the least impact on the attitude towards telemedicine. Conclusion: Health care professionals play a significant role in the effective implementation and sustainability of telemedicine. However, most participating healthcare professionals had no adequate knowledge of telemedicine despite their satisfied attitude towards it. Variations in attitude exist among the different groups of healthcare professionals. Therefore, there is a need to establish tailored educational interventions for healthcare professionals to ensure the proper implementation and sustainability of telemedicine.